Mutational landscape of nodal peripheral T-cell lymphoma subtypes. (October 2021) - Tomas-Roca, Laura; Rodriguez, Marta; Alonso-Alonso, Ruth; Cereceda, Laura; Rodríguez-Pinilla, Socorro M; Borregon, Jennifer; Manso, Rebeca; Villaescusa, Teresa; Córdoba, Raúl; Sánchez-Beato, Margarita; Fernández-Miranda, Ismael; Bárcena, Carmen; et al.
Abstract : Introduction: Nodal peripheral T-cell lymphoma (PTCL) subclassification (Angioimmunoblastic TCL, PTCL-with T Follicular Helper phenotype and PTCL-NOS) and therapeutic targeting is still controversial. Overall survival (OS) is only around 30% after 5 years. Methods: We performed targeted next-generation sequencing of 61 selected genes in 76 PTCL patients. Among the 76cases, 44 were classified as AITL, 18 as PTCL-TFH and 14 as PTCL-NOS. Results: Our analysis revealed a wide variety of genetic variants that possibly drive the development of AITL, PTCL-TFH and/or PTCL-NOS. We identified an average of 4 variants per patient, mainly clustered in genes regulating chromatin conformation (TET2, DNMT3A) and T-cell differentiation (RHOA, MTOR, IDH2, VAV1 and NOTCH1). More frequently mutated genes were TET2 (76, 31%) and DNMT3A (27, 63%). Multiple mutations were found in TET2, VAV1, RHOA, NOTCH1, MTOR, JAK1, ZEB1, ATM, DNMT3A and ARID1B. Main difference among the three Nodal PTCL classes was the higher frequency of RHOAG17V mutations (p<0.0001), present approximately 2 times more frequently in AITL cases (34, 09%) than in PTCL-TFH (16, 66%), and they were not detected in PTCL-NOS. All three Nodal PTCL subtypes share finding suggesting Clonal Hematopoiesis (CH) in TET2 and DNMT3A genes. Cases with higher variant allele frequencies (VAF)s in TET2 and DNMT3A genes vs. other mutated genes were attributed to CH. In our study we found this phenomenon to take place in all Nodal PTCL subtypes (AITL: 31, 8%; PTCL-TFH: 50%; PTCL-NOS: 35, 71%). A correlation was not found between specific mutations, mutational index, mutations attributed to CH and clinical outcome. Conclusions: There is a common molecular basis for the three Nodal PTCL with very frequent mutations in genes regulating chromatin conformation associated with mutations in genes governing T-cell differentiation. RHOA G17V mutations were highly significant enriched in AITL. Findings suggesting Clonal Hematopoiesis were found in the three types of nodal PTCL.